Revision of the genus Physoclypeus Hendel, 1907 (Diptera, Lauxaniidae), with description of seven new species - Mello, Ramon Luciano; Silva, Vera Cristina (Papéis Avulsos de Zoologia, 2008)
The genus Physoclypeus Hendel, 1907 has its distribution restricted to the Neotropical region. In this study, its species have been redescribed, three new combinations have been proposed, three lectotypes have been designated, seven new species have been described, and an identification key to the species is presented. An updated list of species of Physoclypeus is presented as: P. annulatus Hendel, 1925; P. coquilletti (Hendel, 1908); P. farinosus (Hendel, 1925); P. flavus (Wiedemann, 1830); P. hendeli sp. nov. (Type locality, Jamaica, N. Irish Town); P. lineatus (Williston, 1896) new comb.; P. montanus (Becker, 1919) new comb.; P. plaumanni sp. nov. (Type locality, Brazil, Santa Catarina); P. risaraldensis sp. nov. (Type locality, Colombia, Risaralda); P. saltensis sp. nov. (Type locality, Argentina, Salta); P. scutellatus (Curran, 1926) new comb.; P. unimaculatus sp. nov. (Type locality, Mexico, Vera Cruz); P. vitattus sp. nov. (Type locality, Brazil, Santa Catarina) and P. zebrinus sp. nov. (Type locality, Costa Rica, Limón).